Hazardous alcohol consumption among older adults: A comprehensive and multi-national analysis of predictive factors in 13, 351 individuals. Issue 1 (21st December 2020) - Listabarth, Stephan; Vyssoki, Benjamin; Waldhoer, Thomas; Gmeiner, Andrea; Vyssoki, Sandra; Wippel, Andreas; Blüml, Victor; Gruber, Maria; König, Daniel
Abstract: Background: Older adults exhibit heightened vulnerability for alcohol-related health impairments. Increases in the proportion of older adults within the European Union's total population and prevalence rates of alcohol use disorders in this age group are being observed. This large scale international study was conducted to identify those older adults with an increased risk to engage in hazardous drinking behaviour. Methods: Socio-demographic, socio-economic, personality characteristics (Big Five Inventory, BFI-10 ), and alcohol consumption patterns of 13, 351 individuals from 12 different European countries, collected by the Survey of Health, Aging, and Retirement in Europe, were analyzed using regression models. Results: Age, nationality, years of education, as well as personality traits, were significantly associated with alcohol intake. For males, extraversion predicted increased alcohol intake (RR = 1.11, CI = 1.07–1.16), whereas conscientiousness (RR = 0.93, CI = 0.89–0.97), and agreeableness (RR = 0.94, CI = 0.90–0.99), were associated with a reduction. For females, openness to new experiences (RR = 1.11, CI = 1.04–1.18) predicted increased alcohol intake. Concerning excessive drinking, personality traits, nationality, and age-predicted consumption patterns for both sexes: Extraversion was identified as a risk factor for excessive drinking (OR = 1.15; CI = 1.09–1.21), whereas conscientiousness was identified as a protective factor (OR = 0.87; CI = 0.823–0.93). Conclusion: Hazardous alcohol consumption in the elderly was associated with specific personality characteristics. Preventative measures, crucial in reducing deleterious health consequences, should focus on translating the knowledge of the association of certain personality traits and alcohol consumption into improved prevention and treatment.